Pengaruh Celebrity Endorser dan Brand Image Terhadap Keputusan Pembelian Produk Nivea Bodylotion - Sarumaha, Didit Ekosafrial; Tobing, Fitriani; Darmansyah , Muthya Rahmi; Royani , Ida (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The purpose of this study was to determine and analyze the influence of celebrity endorsers and brand image on purchasing decisions for Nivea Body Lotion Products. The population in this study were consumers who purchased Nivea Body Lotion Products, where the sample taken was 93 consumers using the Slovin formula. The data collection technique used in this study was by distributing questionnaires. The analysis technique used in this study was multiple linear regression, partial test (t-test), simultaneous significance test (F-test) and coefficient of determination.The results of the study showed that the variables celebrity endorser and brand image influenced purchasing decisions for Nivea Body Lotion Products. With F count (134.533)> F table (3.1) with a significance level of 0.000. Furthermore, the R Square value is 0.758 which means that there is a relationship between celebrity endorsers and brand image on purchasing decisions, while for R Square it is 0.749 or 74.9% which means that there is an influence of celebrity endorsers and brand image on purchasing decisions, while the remaining 25.1% is another variable that was not studied